2023
DOI: 10.26599/bsa.2023.9050009
|View full text |Cite
|
Sign up to set email alerts
|

Cortico–subcortical spatiotemporal dynamics in Parkinson’s disease can be modulated by transcranial alternating current stimulation

Abstract: Objective: We investigated changes in cortico–subcortical spatiotemporal dynamics to explore the treatment mechanisms of transcranial alternating current stimulation (tACS) in patients with Parkinson’s disease (PD). Methods: Resting-state functional magnetic resonance imaging (rs-fMRI) data were collected from 20 patients with PD and 20 normal controls (NC). Each patient with PD received successive multidisciplinary intensive rehabilitation treatment and tACS treatment over a one-year interval. Individual func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…We have previously conducted a study on 4 Hz tACS in PD using cortico-subcortical co-activation pattern (CAP) analysis on rs-fMRI data, which demonstrated that cortical and subcortical regions exhibit co-activation during the resting state and form distinct CAPs. Moreover, the occurrence of cortical and subcortical CAPs can be enhanced following tACS treatment [ 82 ]. This alteration in brain function may precede the observed behavioral changes.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously conducted a study on 4 Hz tACS in PD using cortico-subcortical co-activation pattern (CAP) analysis on rs-fMRI data, which demonstrated that cortical and subcortical regions exhibit co-activation during the resting state and form distinct CAPs. Moreover, the occurrence of cortical and subcortical CAPs can be enhanced following tACS treatment [ 82 ]. This alteration in brain function may precede the observed behavioral changes.…”
Section: Discussionmentioning
confidence: 99%